ÉLABORATION D’UN BIOFILM DE CONSERVATION ALIMENTAIRE À PARTIR DU MUCUS D’ESCARGOT Helix aspersa muller - BELAYACHI, Imene (My University, 2024)
Food preservation is a major challenge for the food industry, which is looking for effective ways to extend the life of products while ensuring their safety and quality. The objective of this study is the development of a food conservation biofilm from snail mucus Helix aspersa müller, a natural and potentially sustainable alternative to synthetic preservatives. Mucus collection was stimulated by vaporizing snails with 3% Na Cl. The characterization of our biofilm shows a good visual appearance, a thickness of 0.06 mm, a humidity of 25%, a solubility in water ranging from 98.1%, while the transparency is 6.52 0.03%. The application of biofilm mixture in coating solution for strawberries showed after the study that it has a positive effect on the service life of strawberries.
Keywords: Snail; Helix aspersa muller; mucus; biofilm; conservation